The Influence Of Transformational Leadership And Job Satisfaction By Motivating Employee Performance At KSP CU. Damai Sejahtera Medan - Irvan Malay; Adilman Harefa; Ardyn Sari Sinaga; Rahmat Kurniawan (Yayasan Multidimensi Kreatif, 2025)
This study aims to test the effect of transformational leadership and work satisfaction, which is mediated by motivation, on employee performance in the CUSA of Line Banjam (KSP) CU. Peace Seperate Medan. This research uses quantitative approach with survey design. Data obtained through questionnaire that was spreaded to 120 employees working in KSP CU. Peace Seperate Medan. The results of the analysis using multiple linear regression suggest that transformational leadership, job satisfaction, and motivation has a significant effect on employee performance. In addition, motivation proves to mediate the relationship between transformational leadership and job satisfaction on employee performance. This study provides important insights for KUP CS management. Peace to improve employee performance through inspirational leadership, high work satisfaction, and sustainable motivation.